Wild horse spring - Kline, Lisa Williams, 1954- (Sisters in all seasons ;, 2012)
While vacationing in a beach house surrounded by wild horses on North Carolina's Outer Banks, two very different stepsisters who like the same boy must band together to prove his innocence when he is accused of committing a crime against the horses.